Countercurrent gas-solid trickle flow reactor with structured packing: Hydrodynamics and CaO-CO2 reaction - Obradović, Ana; Levec, Janez (AIChE journal, 2015)
The sorption reaction CaO–CO2 was examined in a countercurrent gas–solid trickle flow reactor with regularly stacked packing at T = 500–600°C, pCO2 = 40–50 kPa, solid‐phase fluxes S = 0.3–0.5 kg m−2 s−1, and CaO particles of 500–710 μm in size. Sorption kinetics was evaluated by thermogravimetric (TG) technique. The random pore model was used for the description of the carbonization reaction. Hydrodynamic characteristics of gas–solid trickle flow were estimated at room temperature and ambient pressure. Plug flow model of both gas and solid‐phase, with the parameters obtained from TG and hydrodynamics experiments, satisfactorily described the sorption process in countercurrent gas–solid trickle flow reactor. © 2015 American Institute of Chemical Engineers AIChE J, 61: 1601–1612, 2015